Peningkatan Kapasitas Produksi dan Pemasaran UMKM Roti Panggang di Desa Setro melalui Teknologi Tepat Guna Berbasis Green Economy - Muzakki, Muzakki; Waras, Waras; Nugroho, Wahyu (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2026)
This Student Creativity Program (PKM) aims to enhance the production capacity and quality of the fish bread enterprise through the implementation of appropriate technology grounded in the principles of the green economy, emphasizing environmental sustainability. The program focuses on the development and application of environmentally friendly production tools, including an energy-efficient electric oven with an automatic temperature controller, stainless-steel corrosion-resistant molds, and hygienic anti-rust worktables. These technological innovations are designed to improve energy efficiency, reduce production time, and ensure food safety and hygiene in accordance with Good Manufacturing Practice (GMP) standards. The implementation results demonstrate an increase in production capacity by 30–50%, achieving more uniform and hygienic product quality while simultaneously reducing carbon emissions through decreased reliance on firewood. Beyond production improvement, the program also encompasses training in financial management and digital marketing to expand market reach and enhance the partner’s competitiveness. This holistic approach fosters the transformation of small-scale enterprises toward sustainable business models that integrate economic efficiency, social welfare, and environmental preservation.